Minimally Invasive and Regenerative Therapeutics. Issue 1 (22nd November 2018) - Ashammakhi, Nureddin; Ahadian, Samad; Darabi, Mohammad Ali; El Tahchi, Mario; Lee, Junmin; Suthiwanich, Kasinan; Sheikhi, Amir; Dokmeci, Mehmet R.; Oklu, Rahmi; Khademhosseini, Ali
Abstract: Advances in biomaterial synthesis and fabrication, stem cell biology, bioimaging, microsurgery procedures, and microscale technologies have made minimally invasive therapeutics a viable tool in regenerative medicine. Therapeutics, herein defined as cells, biomaterials, biomolecules, and their combinations, can be delivered in a minimally invasive way to regenerate different tissues in the body, such as bone, cartilage, pancreas, cardiac, skeletal muscle, liver, skin, and neural tissues. Sophisticated methods of tracking, sensing, and stimulation of therapeutics in vivo using nano‐biomaterials and soft bioelectronic devices provide great opportunities to further develop minimally invasive and regenerative therapeutics (MIRET). In general, minimally invasive delivery methods offer high yield with low risk of complications and reduced costs compared to conventional delivery methods. Here, minimally invasive approaches for delivering regenerative therapeutics into the body are reviewed. The use of MIRET to treat different tissues and organs is described. Although some clinical trials have been performed using MIRET, it is hoped that such therapeutics find wider applications to treat patients. Finally, some future perspective and challenges for this emerging field are highlighted. Abstract : Current and future minimally invasive and regenerative therapeutics are reviewed together with delivery routes and tools. Regenerative therapeutics based on cells, biomaterials, biomolecules, and their combinations for different organs are described. The integration of minimally invasive approaches with robotics, regenerative therapeutics, and imaging techniques is also introduced. In addition, related challenges and future directions are discussed.